Analisis Sikap Dan Preferensi Petani Terhadap Penggunaan Benih Padi Varietas Unggul di Kabupaten Langkat Sumatera Utara - Tommy Purba; Kelin Tarigan; Tavi Supriana (JURNAL AGRICA, 2022)
Farmers are the leading agricultural businesses, attitude and preferences of farmers to choosevarieties of rice are very important because farmers have the dual role as a producer and concumer.The purpose of this research is to identify and analyze attitudes and preferences farmers with seedsuperior rice varieties. The research areas which were selected purposively, that is conducted invillages Purwobinangun Sei Bingai district Langkat, North Sumatra Province. The research was donein september 2020-februari 2021.The data used in the form of primary and secondary. The method ofanalysis that used the multiatribut fishbein Model and Conjoin analysis .The results from the study isthat the most farmers purwobinangan langkat district , preferred varieties inpari 32 than ciherangand mekongga because it has a lead in attributes high productivity , hold the power of growing pestand disease and high germinating. Sample farmers preference on the use of seed rice varieties aheadlike seed 7-9 tons of rice with high productivity, types of rice pulen because it is easily marketed forhousehold consumption, pest and disease resistant, the price of grain Rp. 650.000/quintal, packagingseeds with size 10 kg, and the purchase of seeds in the small shop.